2011
DOI: 10.1080/09540121.2011.596517
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of community- and family-level injection drug user (IDU)- and HIV-related stigma, disclosure decisions and experiences with layered stigma among HIV-positive IDUs in Vietnam

Abstract: This paper explores how perceived stigma and layered stigma related to injection drug use and being HIV positive influence the decision to disclose one’s HIV status to family and community and experiences with stigma following disclosure among a population of HIV positive male injection drug users (IDUs) in Thai Nguyen, Vietnam. In qualitative interviews conducted between 2007 and 2008, 25 HIV positive male IDUs described layered stigma in their community but an absence of layered stigma within their families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 15 publications
5
71
0
Order By: Relevance
“…Although most PLHIV were recruited from HIV clinics where they had access to HIV care and treatment, they often began treatment at an advanced disease-stage. As documented in earlier studies (Hong, et al, 2004; Rudolph, et al, 2012; Thi, et al, 2008), we found that layered stigma hindered disclosure of HIV infection and might discourage some from seeking HIV-related services, leading to poor health and limiting employment. Thus, HIV created both social and physical barriers to community reintegration.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although most PLHIV were recruited from HIV clinics where they had access to HIV care and treatment, they often began treatment at an advanced disease-stage. As documented in earlier studies (Hong, et al, 2004; Rudolph, et al, 2012; Thi, et al, 2008), we found that layered stigma hindered disclosure of HIV infection and might discourage some from seeking HIV-related services, leading to poor health and limiting employment. Thus, HIV created both social and physical barriers to community reintegration.…”
Section: Discussionsupporting
confidence: 81%
“…The relatively fewer reports of family-level stigmatization compared to previous research (Hong, et al, 2004; Rudolph, et al, 2012) may reflect participants’ long histories of drug addiction and lengthy detainments, which may have provided opportunities for families to either remove their support, as some wives had done through separation and divorce, or rework their relationships with these men. Additionally, over half of our sample consisted of PLHIV, who experienced a greater level of acceptance both in our current and previous study (Rudolph, et al, 2012) likely because illness helped reorient families’ perceptions of participants from partaking in morally problematic behavior, towards a sick relative needing care and support.…”
Section: Discussionmentioning
confidence: 69%
“…Layered stigma also exists as PLWH are likely to belong to marginalized populations (Rudolph et al, 2012). The sources of discrimination include the general public, health care professionals as well as family members of the PLWH (Anderson et al, 2003;Williams et al, 2006;Zhao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the work on gay male sex workers, the bulk of the research on intersecting or "layered stigma" focuses on the relationship between HIV stigma with other coexisting stigmas, such as injection drug use (Rudolph et al 2012) and co-infection with hepatitis C (Lekas et al 2011). These studies focus on health and psychological effects of layered stigmas, and the distinction between felt and enacted stigma (Lekas et al 2011).…”
Section: Intersecting Stigmasmentioning
confidence: 99%